Exceptional Antioxidant, Non‐Cytotoxic Activity of Integral Lemon Pectin from Hydrodynamic Cavitation. Issue 17 (4th May 2020) - Nuzzo, Domenico; Cristaldi, Laura; Sciortino, Marzia; Albanese, Lorenzo; Scurria, Antonino; Zabini, Federica; Lino, Claudia; Pagliaro, Mario; Meneguzzo, Francesco; Di Carlo, Marta; Ciriminna, Rosaria
Abstract: Lemon pectin extracted along with water‐soluble flavonoids and other phytochemicals from citrus industry's waste lemon peel via hydrodynamic cavitation in water, directly at pre‐industrial scale and further isolated via freeze drying, shows exceptionally high antioxidant and non‐cytotoxic activity. Preliminary investigation indicates also significant antimicrobial activity. These findings open the route to the development of new nutraceutical and healthcare applications of a versatile biopolymer endowed with new functionality, rapidly and conveniently obtained from an abundant by‐product of the agri‐food industry. Abstract : Dubbed IntegroPectin, lemon pectin extracted along with water‐soluble flavonoids and other phytochemicals from waste lemon peel via hydrodynamic cavitation in water directly at pre‐industrial scale and further isolated via freeze drying, shows exceptionally high antioxidant and non‐cytotoxic activity. Preliminary investigation indicates also significant antimicrobial activity. New nutraceutical and healthcare applications of a versatile biopolymer endowed with new functionality are anticipated.